Promoting and enhancing the graduate student transition experience : an exploratory study of Kansas State University - Lopez, Kathryn T. (Kansas State University, 2013)
This is an exploratory study on the existing transition efforts of the Kansas State University Graduate School for master’s degree students. There are a variety of graduate students at Kansas State University with many different graduate program experiences. This study identifies the current status of incoming master’s degree students outreach and details experiences of transitioning graduate students to make suggestions on future strategies. It is vital to identify if, and which, programs are catering to the different needs of these students during their socialization into their graduate program. The study has three main objectives: (1) determine the level of personal contact and emphasis on relationship-building during a master’s degree student’s transition, (2) identify the general efforts and practices of specific master’s degree programs and the Kansas State University Graduate School, and (3) to document the needs of students as they transition into graduate school at Kansas State University. The research was conducted through use of confidential one-on-one in-depth interviews with nine Kansas State University graduate program directors and two Graduate School administrators. Ten newly admitted to the Kansas State University graduate program in the spring of 2013 were interviewed. The qualitative approach to this study enabled the researcher to get detailed testimonials and experience-based knowledge from all of these key stakeholders. Overall, the study revealed that graduate students value face-to-face and personal interaction and showed that student-to-student contact is a preferred component to a successful socialization of graduate students. The needs of transitioning graduate students included assistance with course scheduling, assistantship responsibilities, advisor selection, and an overall understanding that graduate school is different from undergraduate school. Future graduate program strategies that would assist in the successful socialization of graduate students include: orientations, meeting with graduate program directors, social and networking opportunities, and workshops. Involvement in student organizations and utilization of on-campus resources are also a part of most of the graduate programs, and graduate school transition outreach. Based on the findings of this study, the researcher offers suggestions to the Graduate School, graduate programs, and incoming students in order to help enhance the transition experience of master’s degree students into graduate school at Kansas State University.
Keywords: Graduate student transition; Relationship management theory; Graduate school outreach; Strategic communication; Master's degree student needs; Graduate school transition efforts; Higher Education (0745); Mass Communications (0708); Social Sciences Education (0534)